(untitled) (ILMIY TADQIQOTLAR VA YANGI OLAM, 2026)
Annotatsiya. Ushbu maqolada Surxondaryo viloyati Jarqo‘rg‘on tumani shevalarida kundalik turmushga oid leksik birliklarning izoglossalari tahlil qilinadi. Tadqiqotda oziq-ovqat, qishloq xo‘jaligi va kiyim-kechak bilan bog‘liq so‘zlarning hududiy tarqalishi ,ularning fonetik va leksik variantlari hamda shevalararo farqlari aniqlanadi. Izoglossalar orqali mazkur birliklarning geografik chegaralari belgilab beriladi. Tadqiqot natijalari o‘zbek dialektologiyasi va areal lingvistika Abstract. In this article, the isoglosses of lexical units related to everyday life in the dialects of the Jarkurgan district of Surkhandarya region are analyzed. The study identifies the territorial distribution of words related to food, agriculture, and clothing, their phonetic and lexical variants, as well as dialectal differences. Through isoglosses, the geographical boundaries of these units are determined. The research results serve as an important source in the field of Uzbek dialectology and areal linguistics.